Using Toronto to Explore Three Suburban Stereotypes, and Vice Versa. (January 2015) - Harris, Richard
Urbanists share and reproduce three stereotypes about North American suburbs. First, many invoke a clichéd ideal: the desire to enjoy quiet privacy in a low-density residential environment near the urban fringe. Second, they assume that most suburbs have actually conformed to this ideal. Third, academics and planners alike agree on a stereotypical judgment: suburbs are to be deplored. This synthetic essay argues that residential patterns in postwar Toronto never conformed to these stereotypes: especially since the 1970s it has harboured a competing, more urbane popular ideal; its suburbs have been socially and physically diverse; and, recognizing diversity, local urbanists have made varied judgments. Suburban diversity has become systematized since the 1970s, so that a new local stereotype has emerged: that of the declining inner suburb. Toronto's experience exemplifies that of one of the two main types of North American metro. It challenges stereotypes, while those stereotypes illuminate its particular character. Most generally, while polycentricity and dispersion have shaped its economic geography, the language of zones is still meaningful in interpreting its residential patterns. There may be a larger lesson there.